#### Answer

(-4x+1)(x+6)

#### Work Step by Step

-4$x^{2}$-23x+6=-4$x^{2}$-24x+x+6=
-4x(x+6)+1(x+6)=(-4x+1)(x+6)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

(-4x+1)(x+6)

-4$x^{2}$-23x+6=-4$x^{2}$-24x+x+6=
-4x(x+6)+1(x+6)=(-4x+1)(x+6)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.